IBM Business Process Manager operations guide - Brown, Bryan; Carlson-Neumann, Karri S.; Filley, Mark; Gu, Weiming; Richardson, Chris; Spriet, Dave; Zhang, Shuo (Redbooks, 2016)
This IBM® Redbooks® publication provides operations teams with architectural design patterns and guidelines for the day-to-day challenges that they face when managing their IBM IBM Business Process Manager (BPM) infrastructure. Today, IBM BPM L2 and L3 Support and SWAT teams are constantly advising customers how to deal with the following common challenges: Deployment options (on-premises, patterns, cloud, and so on) Administration DevOps Automation Performance monitoring and tuning Infrastructure management Scalability High Availability and Data Recovery Federation This publication enables customers to become self-sufficient, promote consistency and accelerate IBM BPM Support engagements. This IBM Redbooks publication is targeted toward technical professionals (technical support staff, IT Architects, and IT Specialists) who are responsible for meeting day-to-day challenges that they face when they are managing an IBM BPM infrastructure.